Exploration on the Approaches of Diverse Sedimentations in Polyphenol Solutions: An Integrated Chain of Evidence Based on the Physical Phase, Chemical Profile, and Sediment Elements - Huang, Hao-zhou; Feng, Bi; Lin, Jun-zhi; Zhao, Sheng-yu; Ma, Hong-yan; Liu, Hai-yan; Fan, San-hu; Wu, Zhen-feng; Xu, Run-chun; Han, Li; Zhang, Ding-kun (Frontiers in Pharmacology, 2019)
Triphala is a famous herbal formula originated in Asia and is popular in America. Due to the high abundance of polyphenols, its oral liquid is unstable and easy to cause precipitate, which results in the loss of activities. However, complex composition and unclear precipitation mechanism hinders the improvement of stability. In this study, the accumulation of precipitation in the storage and its effect on activity were investigated. Then, an integrated chain of evidence was proposed based on the physical phase, chemical profile and sediment elements. The results showed that antioxidant activity decreased from IC50 115μL to 146μL before and after 90 days of storage, and the anti-fatigue activity decreased from 30.54 min to 28.47 min. Turbiscan Lab Expert observed that particle size increased from 106 nm to 122 nm, and the turbiscan stability index increased from 0 to 14, which indicated that its stability is continuously decreasing. HPLC fingerprint coupled with multivariate statistical analysis identified these chemical markers changed significantly, such as gallic acid, catechins and ellagic acid, et al. Loss of catechins tend to be involved in the formation of phlobaphene precipitation. The fact that the new-born ellagic acid in precipitation (0.47mg/mL) is significantly higher than that reduce in solution (0.25mg/mL) indicates that is not only derived from colloid aging. Microscopic observation combined with energy spectrum analysis further confirmed the existence of the multi-precipitates. The crystalline precipitate is ellagic acid, and the other is phlobaphene. In conclusion, based on the evidence chain a nalysis, this study revealed a systematic changes of the whole polyphenols solution system. It provides a novel perspective to understand the sedimentation formation of polyphenols solution, which is an important theoretical contribution to the preparation of polyphenol solutions.